Oral HIV-Associated Kaposi Sarcoma: A Clinical Study from the Ga-Rankuwa Area, South Africa - Razia A. G. Khammissa; Liron Pantanowitz; Liviu Feller (AIDS Research and Treatment)
Background. Kaposi sarcoma (KS) is one of the most common neoplasms diagnosed in HIV-seropositive subjects. Oral involvement is frequent and is associated with a poor prognosis. The aim of this study was to characterize the features of oral HIV-KS in patients from Ga-Rankuwa, South Africa. Methods. All cases with confirmed oral HIV-KS treated at the oral medicine clinic in Ga-Rankuwa from 2004 to 2010 were included in this retrospective study. Differences between males and females with oral HIV-KS in relation to HIV infection status, to oral KS presentation and to survival rates were statistically analysed. Results. Twenty (54%) of the 37 patients in the study were females and 17 (46%) were males. In 21 patients (57%), the initial presentation of HIV-KS was in the mouth. Other than the fact that females presented with larger (≥10 mm) oral KS lesions (P=0.0004), there were no statistically significant gender differences. Significantly more patients presented with multiple oral HIV-KS lesions than with single lesions (P=0.0003). Nine patients (24%) developed concomitant facial lymphoedema, and these patients had a significantly lower CD4+ T-cell count (28 cells/mm3) compared to the rest of the group (130 cells/mm3) (P=0.01). The average CD4+ T-cell count of the patients who died (64 cells/mm3) was significantly lower (P=0.0004), there were no statistically significant gender differences. Significantly more patients presented with multiple oral HIV-KS lesions than with single lesions (P=0.016) at the time of oral-KS presentation than of those who survived (166  cells/mm3). Conclusions: In Ga-Rankuwa, South Africa where HIV-KS is prevalent, oral KS affects similarly males and females. A low CD4+ T-cell count at the time of oral HIV-KS diagnosis and the development of facial lymphoedema during the course of HIV-KS disease portends a poor prognosis.